Strategic PIAO communication for Public Value creation in Local Government - Alberto Trinchini; Fabio Zuccarini; Marco Berardi; Andrea Ziruolo (European Conference on Knowledge Management, 2026)
Public administrations are increasingly expected to create Public Value through transparency, participation, organizational alignment and trust, not only through service delivery. This paper examines how investments in communicating the Piano Integrato di Attività e Organizzazione - Integrated Activity and Organization Plan (PIAO) may contribute to the organizational conditions enabling Public Value creation. Building on Knowledge Management, Organizational Learning, Public Value Governance, Public Service Motivation and strategic communication literature, the study conceptualizes the PIAO as a Knowledge Management infrastructure whose effectiveness depends on whether its strategic content is understood and translated into everyday practices. Adopting a qualitative conceptual approach supported by an exploratory case study of the Municipality of Pescara (Italy), the paper develops the Public Value Promotion Investment Indicator (PVP-II), a managerial tool for estimating the organizational effort devoted to promoting Public Value through internal communication, external communication, training, stakeholder engagement and employee involvement. Rather than measuring Public Value itself, the PVP-II estimates investments in knowledge-sharing processes that facilitate strategic alignment, organizational learning, employee engagement, institutional trust and stakeholder awareness. The paper contributes to Knowledge Management research by positioning communication as a strategic organizational investment connecting integrated planning, knowledge processes and Public Value creation.